1989
DOI: 10.1128/jcm.27.7.1661-1663.1989
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of pulmonary toxoplasmosis in patients with acquired immunodeficiency syndrome

Abstract: In four cases of pulmonary toxoplasmosis occurring in patients with acquired immunodeficiency syndrome, Toxoplasma sp. was discovered in bronchoalveolar-lavage fluid (three cases) and in lung biopsy specimen (one case) by using the following methods: direct examination of smears stained with eosine-methylene blue fast stain, indirect immunofluorescence assay, and inoculation of MRC5 fibroblast cell line in tissue culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…3,26,125 Immuno histochemistry and tissue culture have been recommended for lung biopsies and BAL specimens from human patients with acquired immunodeficiency syndrome (AIDS). 133,134 Treatment There appears to be no published work comparing the clinical efficacy of drugs used to treat feline toxoplasmosis. A study of clindamycin efficacy in an experimental model of acute toxoplasmosis demonstrated that there was increased morbidity and mortality from hepatitis and interstitial pneumonia in both clindamycin treatment groups (12.5 mg/kg q12h PO and 11 mg/kg q24h PO) compared with both control groups (placebo once or twice daily PO).…”
Section: Toxoplasma Gondiimentioning
confidence: 99%
“…3,26,125 Immuno histochemistry and tissue culture have been recommended for lung biopsies and BAL specimens from human patients with acquired immunodeficiency syndrome (AIDS). 133,134 Treatment There appears to be no published work comparing the clinical efficacy of drugs used to treat feline toxoplasmosis. A study of clindamycin efficacy in an experimental model of acute toxoplasmosis demonstrated that there was increased morbidity and mortality from hepatitis and interstitial pneumonia in both clindamycin treatment groups (12.5 mg/kg q12h PO and 11 mg/kg q24h PO) compared with both control groups (placebo once or twice daily PO).…”
Section: Toxoplasma Gondiimentioning
confidence: 99%
“…Techniques to increase the sensitivity of detection of tachyzoites include preparation of BAL samples by cytocentrifugation and use of immunofluorescent techniques. 22 In humans, diagnosis is further facilitated by PCR and tissue culture of BAL fluid. 23 Serology may be used as an adjunct to diagnosing toxoplasmosis though interpretation is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence of pulmonary toxoplasmosis in HIV‐infected patients with respiratory manifestations suggestive of pneumonia is between 2.2 and 4% [1,24,25]. The clinical presentation of toxoplasmic pneumonitis in HIV‐infected patients can manifest itself in two ways: (1) nodular focal pneumonitis which typically occurs in moderately immunocompromised or immunocompetent patients, and (2) severe, rapidly progressive systemic infection with pulmonary involvement occurring in severely immunocompromised patients [26].…”
Section: Discussionmentioning
confidence: 99%